Historical Occupational Trichloroethylene Air Concentrations Based on Inspection Measurements From Shanghai, China. (1st September 2014) - Friesen, Melissa C.; Locke, Sarah J.; Chen, Yu-Cheng; Coble, Joseph B.; Stewart, Patricia A.; Ji, Bu-Tian; Bassig, Bryan; Lu, Wei; Xue, Shouzheng; Chow, Wong-Ho; Lan, Qing; Purdue, Mark P.; et al.
Abstract : Purpose: Trichloroethylene (TCE) is a carcinogen that has been linked to kidney cancer and possibly other cancer sites including non-Hodgkin lymphoma. Its use in China has increased since the early 1990s with China's growing metal, electronic, and telecommunications industries. We examined historical occupational TCE air concentration patterns in a database of TCE inspection measurements collected in Shanghai, China to identify temporal trends and broad contrasts among occupations and industries. Methods: Using a database of 932 short-term, area TCE air inspection measurements collected in Shanghai worksites from 1968 through 2000 (median year 1986), we developed mixed-effects models to evaluate job-, industry-, and time-specific TCE air concentrations. Results: Models of TCE air concentrations from Shanghai work sites predicted that exposures decreased 5–10% per year between 1968 and 2000. Measurements collected near launderers and dry cleaners had the highest predicted geometric means (GM for 1986 = 150–190mg m −3 ). The majority (53%) of the measurements were collected in metal treatment jobs. In a model restricted to measurements in metal treatment jobs, predicted GMs for 1986 varied 35-fold across industries, from 11mg m −3 in 'other metal products/repair' industries to 390mg m –3 in 'ships/aircrafts' industries. Conclusions: TCE workplace air concentrations appeared to have dropped over time in Shanghai, China between 1968 and 2000. Understanding differences in TCE concentrations across time, occupations, and industries may assist future epidemiologic studies in China.